2018
DOI: 10.1177/2054358118803323
|View full text |Cite
|
Sign up to set email alerts
|

Educational Support Around Dialysis Modality Decision Making in Patients With Chronic Kidney Disease: Qualitative Study

Abstract: Background:Patients with chronic kidney disease (CKD) are asked to choose a renal replacement therapy or conservative management. Education and knowledge transfer play key roles in this decision-making process, yet they remain a partially met need.Objective:We sought to understand the dialysis modality decision-making process through exploration of the predialysis patient experience to better inform the educational process.Design:Qualitative descriptive study.Setting:Kidney Care Centre of London Health Science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 43 publications
2
38
0
1
Order By: Relevance
“…Recent studies have shown that the Surprise Question may be useful in helping clinicians identify poor prognoses and functional statuses as well as frailty among older patients with advanced CKD [38,44,45]. We also found that higher health literacy was associated with preference for supportive kidney care, which reinforces the importance of clear communication and dialogue between clinicians and patients to better assist them in navigating their health decisions [46]. Health literacy has been associated with advance care planningan important consideration for older patients with advanced CKD [47][48][49].…”
Section: Discussionsupporting
confidence: 68%
“…Recent studies have shown that the Surprise Question may be useful in helping clinicians identify poor prognoses and functional statuses as well as frailty among older patients with advanced CKD [38,44,45]. We also found that higher health literacy was associated with preference for supportive kidney care, which reinforces the importance of clear communication and dialogue between clinicians and patients to better assist them in navigating their health decisions [46]. Health literacy has been associated with advance care planningan important consideration for older patients with advanced CKD [47][48][49].…”
Section: Discussionsupporting
confidence: 68%
“…Thirdly, even though the surrogate outcome, the patients' knowledge and confidence in PD were increasing after video counseling, but it was not a significant difference between customized and conventional video counseling group. Deciding to have dialysis depends on many abstract aspects such other than knowledge and confidence in dialysis as personal values, beliefs, and feelings toward life, suffering, death and other patients experience (13)(14)(15)(16). In-depth interviews on this issue should be further evaluated.…”
Section: Discussionmentioning
confidence: 99%
“… 36 This begins with the appropriate incorporation of patients into the research process itself to realize their priorities, values, and experiences in recommendations for practice. 37 , 38 …”
Section: Reviewmentioning
confidence: 99%
“… 62 , 65 - 67 There is a large emotional toll associated with having CKD, especially when it comes to deciding on and initiating dialysis. 38 , 49 , 68 Anxiety, depression, and the emotional impact of dialysis are additional patient quality metrics that must be incorporated into CKD guidelines as they have been shown to predict patient morbidity, mortality, and QOL. 62 Psychologists are considered an essential part of any multidisciplinary RRT educational program.…”
Section: Reviewmentioning
confidence: 99%